(untitled) (Malay Literature, 2012)
This is a study on Muhammad Yusof Ahmad, a pioneer in modern Malay fiction. To explore his contributions, this study focuses on his creative process, specifically in his writing of formal realism fictions such as his short stories and novelette. This study is approached via the writer’s biography and linking it to his era, and the systems of traditional and western education which shaped his creative abilities. His main works entitled "Percintaan Lady Brazil", "Zaman Sari" and Mencari Isteri were selected as samples for analysis. This study reveals that Muhammad Yusof’s creativity is based on his own experiences in life. The structure of his stories can be traced back to the traditional literature of his culture, and elements of realism made their way in to his plot structure due to his exposure to western literature. His works were targeted at new generations, significantly Malay teachers. His works were early attempts of formal realism in the world of modern Malay literature. Keywords: Muhammad Yusof Ahmad, Malay literature, Malay fiction, Majalah Guru